Antiracist medievalisms : from "Yellow Peril" to Black Lives Matter - Hsy, Jonathan Horng (Arc medievalist., 2021)
How do marginalized communities across the globe use the medieval past to combat racism, educate the public, and create a just world? Jonathan Hsy advances urgent academic and public conversations about race and appropriations of the medieval past in popular culture and the arts.0Examining poetry, fiction, journalism, and performances, Hsy shows how cultural icons such as Frederick Douglass, Wong Chin Foo, Alice Dunbar-Nelson, and Sui Sin Far reinvented medieval traditions to promote social change. Contemporary Asian, Black, Indigenous, Latinx, and multiracial artists embrace diverse pasts to build better futures.